The Effectiveness of Added Admixture Additon Superfluid L with the Reduction of Cement and Water Contents on Concrete Characteristics - Huda, M. Miftachul; Kartini, Wahyu; Astawa, Made Dharma (CIVED, 2023)
ABSTRACT Concrete is a complex-composite material. Semen Portland or other hydraulic types of cements, fine aggregates, coarse aggregates, and water, with or without additional substance, are the major materials in making concretes. In this time, the concrete cost more expensive, despite of many infrastructure development that caused higher concretes demand, the increased of concretes cost also caused by the cements high-price as a result of higher PPN value 11% for cement production cost. Cement is highly affected the concrete cost, it is because cement is the major material in forming the concrete that is more expensive than other types of materials. Therefore, it is important to reduce the cement content to press the cost of concrete. This study done by utilizing the variation of added admixture additon superfluid L to reduce the use of cement and water contents by using trial and test method, and slump that was planned 10±2 cm. The reduction of cement for about 5% and 10% from the total weight of cement also there are 4 added variation of content of admixture additon superfluid L, they are 0.5%, 1.0%, 1.5%, dan 2.0% from the cement weight with FAS still about 0,5. According to the test of concrete characteristics such as compressive strength testing, porocity testing, and elastic modulus testing, generally by having more PSA and admixture additon superfluid L, the quality of concrete getting lower from the view of compressive strenght, porocity,or even elastic modulus. There was concrete mixture configuration while it was 28 days, the most effective variation of reduction cement and water content, also the added admixture additon superfluid L 0,5% that possess compressive strenght value around 26,328 MPa ; porocity value around 11,11% ; elastic modulus value about 21950,49 MPa and poisson rasio value around 0,21179. Key Words: water content; cement content; admixture; concrete characteristics.